(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article analyzes the historical development of the Crimean Khanate, its political, social, and economic structure, as well as the main reasons for its decline and the process of its conquest by the Russian Empire. The article covers the relations of the Crimean Khanate with the Celestial Empire, the policies and economic strategies implemented in the Khanate, as well as the processes of cultural development and the fight against external invasions in the country. In addition, attention was drawn to the internal instability of the last stage of the Crimean Khanate and the process of conquest carried out under the influence of Russia’s imperialist policy. The article helps historians and political scientists better understand the process from the formation of the Crimean Khanate to its decline and serves as a scientific source for a comprehensive study of its history.